Life and mental health in limbo of the Ukraine war: How can helpers assist civilians, asylum seekers and refugees affected by the war? - Anjum, Gulnaz; Aziz, Mudassar; Hamid, Hadar Khasrow (Frontiers in Psychology, 2023)
The terror spread by the war disrupts lives and severs families, leaving individuals and communities devastated. People are left to fend for themselves on multiple levels, especially psychologically. It is well documented that war adversely affects non-combatant civilians, both physically and psychologically. However, how the war puts civilians’ lives in a limbo is an under-researched area. This paper focuses on three aspects: 1) how the mental health and well-being of Ukrainian civilians, asylum seekers, and refugees are affected by the war caused limbo; 2) what factors affect this process of being stuck in the limbo of war; and 3) how psychologists and helpers in the war- ridden and host countries can provide meaningful support. Based on the authors’ own practical work with Ukrainian civilians, refugees, and professional helpers during the war, this paper provides an overview of multi-level factors that impact human psyches in a war, and possible ways to help those who are living in the war limbo. In this research and experiential learning-based review, we offer some helpful strategies, action plans, and resources for the helpers including psychologists, counselors, volunteers, and relief workers. We emphasize that the effects of war are neither linear nor equal for all civilians and refugees. Some will recover and return to a routine life while others will experience panic attacks, trauma, depression, and even PTSD, which can also surface much later and can prolong over the years. Hence, we provide experience-based ways of dealing with short-term and prolonged trauma of living with war and post-traumatic stress disorder (PTSD). Mental health professionals and other helpers in Ukraine and in host countries can use these helping strategies and resources to provide effective support for Ukrainians and for war refugees in general.